Pemanfaatan Media Sosial Facebook dalam Penyebaran Informasi Transportasi ke Publik - Satyadharma, Maudhy; Elwan, La Ode; Putra, Zulfikar (Fakultas Ilmu Budaya, Universitas Jambi, 2023)
Social media has now become one of the basic needs for society in fulfilling information. One of the information media that is often used is Facebook. This research focuses on the use of social media Facebook by the Indonesian Ministry of Transportation in disseminating information on transportation sector development to the public. The results of the research found that the Indonesian Ministry of Transportation's Social Media admin was optimal in utilizing Facebook social media as a means of public information with the finding of 1 content a day in the period August-October 2023. However, it was found that the level of public interaction on the Ministry of Transportation's Facebook Account was quite low with comments of visitors continues to show a decline in numbers. This is because people prefer other social media platforms, namely Instagram, which is also owned by the Indonesian Ministry of Transportation. Abstrak Media sosial saat ini sudah menjadi salah satu kebutuhan dasar bagi masyarakat dalam pemenuhan informasi. Salah satu media informasi yang sering digunakan adalah Facebook. Penelitian ini memfokuskan pada pemanfaatan media sosial Facebook oleh Kementerian Perhubungan RI dalam penyebarluasan informasi pembangunan sektor transportasi kepada masyarakat. Hasil penelitian menemukan bahwa admin Media Sosial Kemenhub RI sudah optimal dalam memanfaatkan media sosial Facebook sebagai sarana informasi publik dengan temuan 1 konten sehari dalam rentang periode Bulan Agustus-Oktober 2023. Namun demikian ditemukan bahwa tingkat interaksi masyarakat dalam Akun Facebook Kemenhub ini cukup rendah dimana komentar dari pengunjung terus menerus memperlihatkan penurunan jumlah. Hal ini disebabkan masyarakat lebih menyenangi platform media sosial lainnya yaitu Instagram yang juga dimiliki oleh Kemenhub RI.